STRATEGI PERDAGANGAN GLOBAL DAULAH FATIMIYAH - Fitrah, Nurul; Haeriyah, Hamzah (JSE: Jurnal Sharia Economica, 2025)
This study examines the global trade strategy of the Fatimid Empire and its impact on economic development and social dynamics in the Mediterranean region during the classical Islamic era. Starting from North Africa and then moving the center of power to Cairo, Egypt, the Fatimids took advantage of Egypt's strategic geographic location as a major hub for international trade networks connecting Asia, Africa, and Europe. Fatimid trade policies were characterized by openness, inclusiveness, and high tolerance towards various religious and ethnic communities, in contrast to the protectionist approach adopted by other political powers at the time. A progressive fiscal system, management of trade taxes, and the development of trade infrastructure such as ports and caravanserais were the main foundations of the Fatimid economy's success. This study highlights that trade not only played a role as a productive economic sector, but also as an instrument of diplomacy, the spread of ideology, and social development. These findings emphasize the importance of reviewing classical Islamic trade practices as a reference for developing a modern Islamic economic system that is fair, inclusive, and sustainable amidst the challenges of globalization and current economic.